Loki: Facilitating Remote Instruction of Physical Tasks Using Bi-Directional Mixed-Reality Telepresence - Kumaravel, Balasaravanan Thoravi; Anderson, Fraser; Fitzmaurice, George; Hartmann, Björn; Grossman, Tovi (Proceedings of the 32nd Annual ACM Symposium on User Interface Software and Technology, 2019)
Remotely instructing and guiding users in physical tasks has offered promise across a wide variety of domains. While it has been the subject of many research projects, current approaches are often limited in the communication bandwidth (lacking context, spatial information) or interactivity (unidirectional, asynchronous) between the expert and the learner. Systems that use Mixed-Reality systems for this purpose have rigid configurations for the expert and the learner. We explore the design space of bi-directional mixed-reality telepresence systems for teaching physical tasks, and present Loki, a novel system which explores the various dimensions of this space. Loki leverages video, audio and spatial capture along with mixed-reality presentation methods to allow users to explore and annotate the local and remote environments, and record and review their own performance as well as their peer's. The system design of Loki also enables easy transitions between different configurations within the explored design space. We validate its utility through a varied set of scenarios and a qualitative user study.